Stage 1 Registered Report: Effect of deficient phagocytosis on neuronal survival and neurological outcome after temporary middle cerebral artery occlusion (tMCAo) [version 3; referees: 2 approved] - Julius V. Emmrich; Jonas J. Neher; Philipp Boehm-Sturm; Matthias Endres; Ulrich Dirnagl; Christoph Harms (F1000Research, 2018)
Stroke is a major cause of death and disability worldwide. In addition to neuronal death resulting directly from energy depletion due to lack of blood supply, inflammation and microglial activation following ischemic brain injury has been increasingly recognized to be a key contributor to the pathophysiology of cerebrovascular disease. However, our understanding of the cross talk between the ischemic brain and the immune system is limited. Recently, we demonstrated that following focal ischemia, death of mature viable neurons can be executed through phagocytosis by microglial cells or recruited macrophages, i.e. through phagoptosis. It was shown that inhibition of phagocytic signaling pathways following endothelin-1 induced focal cerebral ischemia leads to increased neuronal survival and neurological recovery. This suggests that inhibition of specific phagocytic pathways may prevent neuronal death during cerebral ischemia. To further explore this potential therapeutic target, we propose to assess the role of phagocytosis in an established model of temporary (45min) middle cerebral artery occlusion (tMCAo), and to evaluate neuronal survival and neurological recovery in mice with deficient phagocytosis. The primary outcome of this study will be forelimb function assessed with the staircase test. Secondary outcomes constitute Rotarod performance, stroke volume (quantified on MR imaging or brain sections, respectively), diffusion tensor imaging (DTI) connectome mapping, and histological analyses to measure neuronal and microglial densities, and phagocytic activity. Male mice aged 10-12 weeks will be used for experiments.